Roadmap to high-energy square pulses in anomalous dispersion fiber lasers - Semaan, G.; Ben Braham, F.; Salhi, M.; Sanchez, François (Photonics Letters of Poland, 2016)
Dissipative soliton resonance (DSR) is a soliton formation where the energy in a dissipative system becomes infinite. In the anomalous dispersion regime, this energy is not limited by the soliton area theorem. Since this phenomenon is wave breaking free, it can be useful in designing fiber lasers generating pulses with relatively high energies. Based on this principle, we have demonstrated the emission of high energetic square pulses from Er:Yb double-clad passively mode-locked fiber lasers using different mode-locking mechanisms. We first show the evolution of pulse width, energy and peak power by varying the pumping power of the amplifier, then we control separately the characteristic of the output square pulse by assigning each one to an amplifier. Experimental results exhibit record energies in fiber lasers up to 10 uJ. Full Text: PDF References W. Chang, A. Ankiewicz, J.M Soto Crespo and N. Akhmediev, " Dissipative soliton resonances", Phys. Rev. A 78, 023830 (2008). CrossRef P. Grelu, W. Chang, A. Ankiewicz, J. M. Soto-Crespo, and N. Akhmediev, "Dissipative soliton resonance as a guideline for high-energy pulse laser oscillators", J. Opt. Soc. Am. B 27, 2336 (2010). CrossRef X. Wu, D. Y. Tang, H. Zhang, and L. M. Zhao, "Dissipative soliton resonance in an all-normal-dispersion erbium-doped fiber laser", Opt. Express 17, 5580 (2009). CrossRef G. Semaan, F. Ben Braham, M. Salhi, Y. Meng, F. Bahloul, and F. Sanchez, "Generation of high energy square-wave pulses in all anomalous dispersion Er:Yb passive mode locked fiber ring laser", Opt. Express 24, 8399 (2016). CrossRef K. Krzempek, "Dissipative soliton resonances in all-fiber Er-Yb double clad figure-8 laser", Opt. Express 23, 30651 (2015). CrossRef L. Mei et al., "Width and amplitude tunable square-wave pulse in dual-pump passively mode-locked fiber laser", Opt. Lett. 39, 3235 (2014). CrossRef X. Zhang et al., "Square-wave pulse with ultra-wide tuning range in a passively mode-locked fiber laser", Opt. Lett. 37, 1334 (2012). CrossRef K. Krzempek, J. Sotor, and K. Abramski, "Compact all-fiber figure-9 dissipative soliton resonance mode-locked double-clad Er:Yb laser", Opt. Lett. 41, 4995-4998 (2016). CrossRef G. Semaan, F. Ben Braham, J. Fourmont, M. Salhi, F. Bahloul, and F. Sanchez, "10uJ dissipative soliton resonance square pulse in a dual amplifier figure-of-eight double-clad Er:Yb mode-locked fiber laser", Opt. Lett. 41, 4767 (2016). CrossRef K. Krzempek and K. Abramski, "Dissipative soliton resonance mode-locked double clad Er:Yb laser at different values of anomalous dispersion", Opt. Express 24, 22379-22386 (2016). CrossRef